(untitled) (Revista Cocar, 2023)
Este artigo delineia o Estado da Arte sobre a pesquisa em Educação Emocional articulada à perspectiva da Formação Humana para apontar como essa proposta vem se desenvolvendo na pós-graduação stricto-sensu brasileira. Foi feito um mapeamento de 67 trabalhos, produzidos entre 1990 e 2019, levantados através do portal CAPES de teses e dissertações. Desse universo, nove trabalhos que articularam, simultaneamente, emoções e formação humana foram analisados interpretativamente, viabilizando a percepção de distintas orientações de Educação Emocional como: a neoliberal, a de formação humana e a híbrida. A principal contribuição está no delineamento de diferentes perspectivas de Educação Emocional e no destaque para uma proposta com fins de formação humana, que se contrapõe ao reducionismo e ao individualismo da lógica neoliberal voltada para o mercado. Palavras-chave: Educação Emocional; Formação Humana; Estado da Arte. Abstract This article outlines the State of the Art on Emotional Education research articulated to a perspective of Human Formation in order to point out how this proposal has been developing in Brazilian stricto-sensu postgraduate studies. A mapping was made of 67 papers, produced between 1990 and 2019, collected through the CAPES portal of theses and dissertations. From this universe, nine papers that simultaneously articulated emotions and human formation were analyzed interpretatively, enabling the perception of distinct Emotional Education orientations such as: neoliberal, human formation, and hybrid. The main contribution is in outlining different perspectives of Emotional Education and in the emphasis on a proposal for human formation purposes that, which is opposed to the reductionism and individualism of neoliberal logic focused on the market. Keywords: Emotional Education; Human Formation; State of the Art.